2015
DOI: 10.7567/apex.8.096601
|View full text |Cite
|
Sign up to set email alerts
|

Simple model-free estimation of orientation order parameters of vacuum-deposited and spin-coated amorphous films used in organic light-emitting diodes

Abstract: Molecular orientation in organic light-emitting diodes (OLEDs) is now regarded as an important factor that affects device efficiency. However, methods to quantitatively estimate the degree of molecular orientation in OLEDs are currently limited, and they require constructing a model of an optical structure. Here, we propose a simple model-free method to estimate the orientation order parameters (S) of molecules in amorphous OLED films from their absorption spectra using the randomization of molecular orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
3
33
0
2
Order By: Relevance
“…All of the methods presented so far require fitting the measured results with simulations using appropriate models, which, in turn, can easily lead to inaccurate or even wrong results if the model itself is inappropriate. Recently, Sakai et al [158] presented a model-free technique to determine TDMV orientation. They used the fact that molecular alignment vanishes if the films are thermally annealed above their glass transition temperature T g , provided that the host material does not crystallize [100,159,160].…”
Section: E Absorption Measurements Before and After Thermal Annealingmentioning
confidence: 99%
“…All of the methods presented so far require fitting the measured results with simulations using appropriate models, which, in turn, can easily lead to inaccurate or even wrong results if the model itself is inappropriate. Recently, Sakai et al [158] presented a model-free technique to determine TDMV orientation. They used the fact that molecular alignment vanishes if the films are thermally annealed above their glass transition temperature T g , provided that the host material does not crystallize [100,159,160].…”
Section: E Absorption Measurements Before and After Thermal Annealingmentioning
confidence: 99%
“…18 The preferential orientation of small emitter molecules for OLEDs has been studied by Yokoyama et al For a number of small molecules they found that the degree of horizontal molecular orientation of small-molecule spin-coated films is inherently lower than that of the corresponding vacuum evaporated films. 19,20 In this study we investigate whether the horizontal alignment of light emitting oligomeric guests in a small molecule host can be induced in layers deposited from solution by varying the aspect ratio of the oligomers. We studied a series of p-conjugated methyl end-capped p-phenylene vinylene oligomers (OPVn), in which the number of phenyl rings, n, varies from 2 to 7 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Cryst. and their Appl., 2020, 20 (1) ≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡ Введение В последнее время актуальным объектом исследований [1] и применений в фотонике и оптоэлектронике [2,3] стали одноосные аморфные молекулярные пленки органических полупроводников, напыленных в вакууме на изотропные подложки. Эти пленки имеют плоскостную ориентацию удлиненных (стержнеобразных или планкообразных) молекул и оптическую ось n, нормальную к подложке.…”
unclassified
“…С физической точки зрения эти пленки интересны тем, что имеют такую же симметрию, как одноосные каламитные термотропные нематики, для которых термодинамически стабильно состояние с аксиальной ориентацией удлиненных молекул относительно n в гомеотропно-ориентированных образцах, а состояние с плоскостной ориентацией удлиненных молекул нестабильно [4] и не наблюдается в природе. Физические и технические свойства пленок определяются характером и степенью ориентационного порядка молекул относительно n [1][2][3]. Поэтому развитие методов исследования ориентационного порядка анизотропных пленок становится актуальной повесткой дня.…”
unclassified